Integrated Business Processes with ERP Systems - Simha R. Magal (John Wiley & Sons, 2012)
Integrated Business Processes with ERP Systems covers the key processes supported by modern ERP systems. This textbook is designed for use as both a reference guide and a conceptual resource for students taking ERP-focused courses using SAP. It examines in depth the core concepts applicable to all ERP environments, and it explains how those concepts can be utilized to implement business processes in SAP systems. Students will gain a deep appreciation for the role of enterprise systems in efficiently managing processes from multiple functional perspectives. Examples of both positive and negative issues associated with enterprise systems are integrated throughout the chapters to illustrate the concepts with real-world experiences. The Wiley Advantage • Integrated Business Processes with ERP Systems approaches topics using an integrated process perspective of the firm. Each process is discussed within the context of its execution across functional areas in the company, with special emphasis on the role of data in managing the coordination between activities and groups. Students will gain a deep appreciation for the role of enterprise systems in efficiently managing processes from multiple functional perspectives. • Running Case Study - Many key examples, demonstrations, and assignments incorporated throughout the book are based on a fictional company, Global Bike Incorporated (GBI). GBI exists virtually in the GBI ERP system, which will be used to provide hands-on experience with executing the various processes in SAP ERP. • Real-World Examples - In addition to the integrated approach and the GBI case study, the text includes multiple scenarios that demonstrate how businesses actually utilize ERP capabilities. Examples of both positive and negative issues associated with enterprise systems are integrated throughout the chapters to illustrate the concepts with real-world experiences. • WileyPLUS resources include the complete book online, recorded demonstrations of each key activity, and interactive hands-on assignments using the SAP platform.